Electrically small folded spherical helix antennas using copper strips and 3D printing technology. Issue 12 (1st June 2016) - Kong, M.; Shin, G.; Lee, S.‐H.; Yoon, I.‐J
Abstract : Folded spherical helix (FSH) antennas using thin and wide copper strips instead of thick wires as a means of reducing the electrical size of ka is designed. It is found that FSH antennas made of copper strips show comparable radiation properties to FSH antennas made of thick wires. Furthermore, such designs can achieve even smaller size down to ka of 0.11 while keeping the radiation quality factors approaching the lower physical bound. An FSH antenna made of copper strips with ka of 0.21 is fabricated as a prototype using 3D printing technology. The measured resonance occurs at 307 MHz with the radiation efficiency of about 90%, verifying the simulated results and the proposed method of utilising copper strips in designing extremely small yet highly efficient volumetric folded helix antennas.